(untitled) (Trabalho & Educação, 2016)
This research aims to understand teaching knowledge which guides teacher’s practices regarding their teaching methods on technical subjects with teacher education in Higher Secondary Technical-Professional Education (HSTPE), at Centro Federal de Educação Tecnológica de Minas Gerais (CEFET-MG). At this level and teaching modality, it is common to find teachers with bachelor’s, master’s and/or doctorate degree, however, without specific training for the teaching profession. The subjects of this study are engineers, bachelors and graduates that have guided, in any initial moment of their graduation, training for the teaching practice. At the beginning of the study, a bibliographical research was carried out. This served as basis for the research object definition as well as methodological issues. The subjects were four teachers and coordinators from CEFET - MG. Data collection was formed by interviews with course coordinators; class observation; questionnaires and interviews with... ___ Esta pesquisa busca compreender o saber docente que orienta a atuação didática de professores de disciplinas técnicas, com formação para a docência, na Educação Profissional Técnica de Nível Médio, no Centro Federal de Educação Tecnológica de Minas Gerais. Geralmente, nesse nível e modalidade de ensino, encontram-se professores bacharéis, com titulação de mestrado e/ou doutorado, contudo, sem uma formação específica para a docência. Os sujeitos desta pesquisa, no entanto, são engenheiros, bacharéis e licenciados que orientaram, em um momento inicial da graduação, sua formação para a docência. Incialmente, para se conhecer as produções do campo, fez-se uma pesquisa bibliográfica. Dela emergiram questões que orientaram a definição do objeto de pesquisa bem como os aspectos metodológicos. Para coleta de dados, além das entrevistas com os coordenadores de curso para identificar os sujeitos da pesquisa, que totalizaram quatro, realizaram- se a observação da atuação didática dos professores, a aplicação de questionários e de entrevistas com...